THE INFLUENCE OF THE PROPORTION OF CAPITAL EXPENDITURES, TOTAL BUMD, INTERGOVERNMENTAL REVENUE AND LOCAL TAXES ON LOCAL GOVERNMENT FINANCIAL INDEPENDENCE AS STRENGTHENING FISCAL DECENTRALIZATION: (Study on Provincial Local Governments in Indonesia 2018-2020) - Icih Icih; Putri Leonita Agustin; Asep Kurniawan (JASS (Journal of Accounting for Sustainable Society), 2023)
This study aims to determine whether the proportion of capital expenditure, the number of BUMD, intergovernmental revenue and local taxes affect the financial independence of local governments as a strengthening of fiscal decentralization. In this study, the number of research samples was 33 provinces. The independen variables are the proportion of capital expenditure, the total of BUMD, intergovernmental revenue and local taxes. Regional financial independence as the dependent variable. This type of research uses quantitative methods using secondary data obtained from DJPK. Methods of data analysis in research using descriptive statistical tests, data quality tests, classical assumption tests, multiple linear regression analysis and hypothesis testing with SPSS. The results showed that partially the variable proportion of capital expenditure and intergovernmental revenue had a negatif effect on regional financial independence, the total of BUMD had no effect on regional financial independence, and regional taxes had a positive effect on regional financial independence. As for simultaneously the results of the study indicate that simultaneously the variable proportion of capital expenditure, the number of BUMD, intergovernmental revenue and regional taxes affect regional financial independence.